Kurt Schumacher; (1950)
II/50-2: Laufzeit: 0h27'12" II/50-3: Laufzeit: 0h52'40" 08.11.1950: Bundestag, Außenpolitische Debatte am 08.11.1950, Laufzeit: 1h19'52"; Bemerkungen: Kurt Schumacher: * 13.10.1895 + 20.08.1952